The Relationship Between Peer Social Support and Academic Resilience Among First-Year Nursing Students in Jakarta - Pratamy, Fadhila Elvian; Tri Setyaningsih; Dian Fitria (Poltekkes Kemenkes Kupang, 2025)
Background: First-year university students often face complex adaptation challenges in higher education, including academic pressure, differing teaching methods, and demands for independence. The ability to persist through such challenges is referred to as academic resilience, which may be influenced by social support from peers. Objective: The purpose of this study is to understand the relationship between peer social support and academic resilience among first-year students in the Bachelor of Nursing Program at STIKes RS Husada Jakarta. Method: The approach adopted was quantitative with a correlational descriptive design and total sampling technique, involving 114 first-semester students. The instrument used was a Likert scale questionnaire to measure both variables. Data were collected using Likert-scale questionnaires and analyzed with the Spearman Rank correlation test due to non-normal distribution. Results: The findings of the study show a significant positive relationship between peer social support and academic resilience (r = 0.459; p < 0.001). This indicates that higher levels of perceived peer support are associated with stronger academic resilience.